An adhesion-related small bowel obstruction occurring within 36 h of a total abdominal hysterectomy and bilateral salpingo-oophorectomy. (7th April 2014) - Shah, Neha; Shah, Sonya Pratik; Thakrar, Amit; Rozati, Hamoun
Abstract : We present a case of adhesion-related small bowel obstruction occurring within only 36 h of a total abdominal hysterectomy and bilateral salpingo-oophorectomy. There has been no previously reported case where there has been such a short interval between surgery and adhesion-related small bowel obstruction. This is important to note, as it ensures that adhesion-related small bowel obstruction is on the list of differential diagnoses for patients who present very soon after surgery with symptoms such as abdominal pain and vomiting. It is also important as it allows the pathogenesis of adhesion formation to be reviewed in light of this rapid onset of adhesion formation and its complications.